State regulation of cluster’ mesosystems in the structure of national economic - Malakhovskyi, Y.; Lizunkov, O.; Savitska, I.; Малаховський, Ю. В.; Лізунков, О. В.; Савіцька, І. М. (ЦНТУ, 2017)
The article summarizes international experience upgrading methodological approaches to the analysis of cluster mesoeconomical systems that occupy an intermediate position between the micro and macro levels of the national economy. The options for the introduction of specialized analytical procedures in the process of analysis of cluster mesosystems in the structure of the national economy are investigated. Special attention is paid to the sectoral and regional clusters. The description of the main stages of the life cycle of clusters of the sectoral and regional profiles is given. The purpose of functioning of cluster` mesosystems which is in the targeted attraction and using of resources of lower level system in order to reach the purpose of functioning of higher level system while using specific tools for the realization of the economic potential of the institutional units within mesoeconomical association is formulated. У статті підсумовано досвід вдосконалення методологічних підходів до аналізу кластерних мезоекономічних систем, що займають проміжне положення між мікро- та макрорівнями національної економіки. Досліджено варіанти впровадження спеціалізованих процедур у процесі проведення аналізу кластерних мезосистем в структурі національної економіки. Особливу увагу приділено галузевим та територіальним кластерам. Описуються основні етапи життєвого циклу функціонування мезоструктур виробничого та регіонального профілю. Сформульовано мету функціонування кластерних мезоекономічних систем, яка полягає у цілеспрямованому залученні та організації використання ресурсів систем нижчого рівня з метою досягнення мети функціонування систем вищого рівня у ході застосування конкретних інструментів для реалізації економічного потенціалу інституційних одиниць у рамках мезоекономічних асоціацій.
Державне регулювання кластерних мезосистем в структурі національної економіки
Keywords: mesoeconomics system; mesoeconomic production system; real economy’ cluster; mesoeconomic territorial system; region cluster; post-industrial society; state regulation; мезоекономічна система; виробнича мезоекономічна система; кластер реальної економіки; мезоекономічна територіальна система; регіональний кластер; постіндустріальне суспільство; державне регулювання